Wearable and Stretchable Strain Sensors: Materials, Sensing Mechanisms, and Applications. (11th June 2020) - Souri, Hamid; Banerjee, Hritwick; Jusufi, Ardian; Radacsi, Norbert; Stokes, Adam A.; Park, Inkyu; Sitti, Metin; Amjadi, Morteza
Abstract : Recent advances in the design and implementation of wearable resistive, capacitive, and optical strain sensors are summarized herein. Wearable and stretchable strain sensors have received extensive research interest due to their applications in personalized healthcare, human motion detection, human–machine interfaces, soft robotics, and beyond. The disconnection of overlapped nanomaterials, reversible opening/closing of microcracks in sensing films, and alteration of the tunneling resistance have been successfully adopted to develop high‐performance resistive‐type sensors. On the other hand, the sensing behavior of capacitive‐type and optical strain sensors is largely governed by their geometrical changes under stretching/releasing cycles. The sensor design parameters, including stretchability, sensitivity, linearity, hysteresis, and dynamic durability, are comprehensively discussed. Finally, the promising applications of wearable strain sensors are highlighted in detail. Although considerable progress has been made so far, wearable strain sensors are still in their prototype stage, and several challenges in the manufacturing of integrated and multifunctional strain sensors should be yet tackled. Abstract : Wearable and stretchable strain sensors have demonstrated promising applications in healthcare and biomedical engineering, sport performance monitoring, and soft robotics. Recent advances in the design of wearable, stretchable, and skin‐mountable strain sensors, and their applications are comprehensively reviewed. The current challenges in the design of multifunctional strain sensors are highlighted, and an outlook is presented.